UTILIZATION OF RICE STRAW WASTE INTO COMPOST FERTILIZER IN GAMPONG COT CUT, KUTA BARO SUB-DISTRICT ACEH BESAR DISTRICT: PEMANFAATAN LIMBAH JERAMI PADI MENJADI PUPUK KOMPOS DI GAMPONG COT CUT KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Husein Abdullah, Umar; Muhammad Afreza; Sri Agustina; Ika Rezvani Aprita; Endiyani; Hardiansyah A; Maghfirah; Mulyanti (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
This Community Service (CS) activity aims to provide information to the community about the utilization of rice straw waste into compost in Gampong Cot Cut, Kuta Baro Sub-district, Aceh Besar District, by utilizing natural resources in the surrounding area so that it can improve the community's economy. Poliven lecturers and students to find out the potential and situation in Gampong Cot Cut Furthermore, planning activities that will be carried out and demonstrated to the community of Gampong Cot Cut. Then the second stage is providing direct explanations to the community about the utilization of rice straw waste in compost fertilizers. The stages of how to make it are: The available rice straw waste is chopped/reduced in size and then mixed with cow dung. Then the EM4 solution is added. The mixture is stirred evenly and tightly closed, and the fermentation process is carried out for 1 month. The CS activity carried out in Gampong Cot Cut, Ingin Jaya Sub-district, Aceh Besar District has been carried out very well and smoothly thanks to the assistance of several parties, namely LPPM Politeknik Indonesia Venezuela, support from the apparatus, and the community of Gampong Cot Cut. This CS activity is useful for developing the potential of the community to be more creative in creating new things, and the community is greatly helped by the demonstration of making rice straw compost.